Influence of the “Smile” program on collaborative learning in virtual education in university students - Cerrón Piñas, Linda Ketty (2023)
The applied research with experimental design, whose general objective was to determine the influence of the "Smile" program on collaborative learning in virtual education in university students of the National University of Central Peru, the rubric of collaborative learning was used in the pre and post test, the population was 350 students, and for the sample 79 UAEG students were considered for the experimental group and 79 students for the control group. The results of both groups show that the p-value is less than 0.05, so we can say that there is a statistically significant difference between the means of the control and experimental groups, concluding that: The "Smile" program significantly influences in the collaborative learning of the students of the National University of central Peru in the virtual modality. to Spanish